A Legal Analysis of the Application of the General Principles of Good Governance (AUPB) as the Basis for Judicial Decision-Making in the Resolution of Administrative Law Disputes - Naufal Hibatul Wafi; Raisa Agnia; Windi Putri Oktapiani; Muhamad Syamsul Maarif; M.Z Syafiq Haidar; Taufiq Alamsyah (Anthroposia: Journal of Social and Human Development, 2026)
This study examines the legal position, judicial application, and future development of the General Principles of Good Governance (AUPB) as a basis for judicial decision making in the resolution of administrative law disputes in Indonesia. Employing a non empirical normative juridical method, the research analyzes constitutional provisions, statutory regulations, administrative law doctrines, and administrative court decisions to evaluate the interaction between legal norms and judicial interpretation. The findings indicate that AUPB has evolved into a significant normative standard within Indonesian administrative law, functioning not only as a complementary legal principle but also as an independent benchmark for reviewing administrative actions and decisions. Judicial practice demonstrates that AUPB serves as an instrument for assessing legality, controlling abuse of authority, guiding the exercise of discretion, and balancing legal certainty with substantive justice. The study also identifies challenges arising from interpretive variation, regulatory fragmentation, and differing judicial approaches to principle based adjudication. Strengthening doctrinal coherence, judicial capacity, and regulatory harmonization is essential for enhancing consistency in administrative adjudication. The research concludes that AUPB plays a central role in reinforcing administrative justice, governmental accountability, and the realization of good governance within the contemporary legal system.